2020
DOI: 10.5194/isprs-annals-v-4-2020-39-2020
|View full text |Cite
|
Sign up to set email alerts
|

A Regression Model of Spatial Accuracy Prediction for Openstreetmap Buildings

Abstract: Abstract. Data quality assessment of OpenStreetMap (OSM) data can be carried out by comparing them with a reference spatial data (e.g authoritative data). However, in case of a lack of reference data, the spatial accuracy is unknown. The aim of this work is therefore to propose a framework to infer relative spatial accuracy of OSM data by using machine learning methods. Our approach is based on the hypothesis that there is a relationship between extrinsic and intrinsic quality measures. Thus, starting from a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…In (Hashemi and Ali Abbaspour, 2015), the authors use the editing history to identify topological inconsistencies. Among approaches using only the data themselves, some use spatial context to analyze the spatial consistency of data (see (Touya and Brando-Escobar, 2013), where the author specifically identify level of detail inconsistencies), while others rely on the geometries of individual objects (Maidaneh Abdi et al, 2020). Some studies concentrate on the history of edition of an object to evaluate its quality (Barron et al, 2014).…”
Section: State Of the Art And Methods Choicesmentioning
confidence: 99%
See 3 more Smart Citations
“…In (Hashemi and Ali Abbaspour, 2015), the authors use the editing history to identify topological inconsistencies. Among approaches using only the data themselves, some use spatial context to analyze the spatial consistency of data (see (Touya and Brando-Escobar, 2013), where the author specifically identify level of detail inconsistencies), while others rely on the geometries of individual objects (Maidaneh Abdi et al, 2020). Some studies concentrate on the history of edition of an object to evaluate its quality (Barron et al, 2014).…”
Section: State Of the Art And Methods Choicesmentioning
confidence: 99%
“…It is about inferring an extrinsic indicator by using intrinsic indicators based on the research hypothesis that the discrepancies between VGI and reference data can be reconstructed from intrinsic indicators. Machine learning methods are used to establish the relationships between intrinsic features and the target extrinsic indicator (Mohammadi and Malek, 2015, Xu et al, 2017, Maidaneh Abdi et al, 2020. The last showed that individual intrinsic indicators gave relevant information about shape accuracy, but that they did not capture absolute accuracy very well.…”
Section: State Of the Art And Methods Choicesmentioning
confidence: 99%
See 2 more Smart Citations
“…When dealing with heterogeneous GI coming from multisources such as different data models, mapping specifications, spatial and temporal scales, as well as non exhaustive or incomplete semantic and thematic information in data sources to be matched, such as for building data, deriving similarity measures that are robust to complex polygons and geometric errors becomes a challenge. Shape measures proved to be efficient for matching polygons datasets since they better distinguish the features between them (Meng and Lu 2014, Fan et al 2014, Xavier et al 2016, Maidaneh Abdi et al 2020. Thus, in the context of heterogeneous GI data matching, there is a need to describe the similarity of polygons in a very fine way.…”
mentioning
confidence: 99%